Planned Concept of Central and External Port as an Opportunity for the Development of Tricity’s Seaports in Poland - Cieczko, M.; Myszka, A.; Kaizer, A. (Scientific Journal of Gdynia Maritime University, 2018)
One of the main determinants of the international status of a seaport is its capacity to handle the largest possible quantities of cargo carried by the largest vessels. A successful seaport is one where trans-shipments are handled by qualified personnel and where excellent facilities are available to ensure that the cargo delivered to the port can be delivered to its destination using the largest possible selection of various modes of transport. A successful seaport should be extended in size to be able to cater for an increasing number of ships at the same time. All these factors can help make seaports more competitive. The largest of Poland’s seaports, namely the Port of Gdańsk and the Port of Gdynia, are trying to reach the status of being ranked among Europe’s best ports. This goal can only be achieved through new ideas and new investment projects. Two projects are planned as a way to stimulate the development of Poland’s seaports: the Central Port at the Port of Gdańsk and the External Port at the Port of Gdynia. These projects will help strengthen the position of Tricity’s seaports in the international arena.